The Status of live corals in Iligan Bay Reefs an analysis of survey results since 1983 and implications to integrated coastal management - Metillo, Ephrime B. (2005)
Over a span of 18 years, assessment of the status of fringing reef had been done for nine years in 17 coastal municipalities along Iligan Bay. A total of 51 reef sites from 46 barangays had been surveyed using the manta tow technique, the line intercept-transect method, the transect-quadrat method, and a combination of these methods. An overlay of result from different studies generated a map showing a temporal mosaic of live coral cover in reef within the jurisdiction of municipal and city governments. If time of data collection was ignored, an analysis of all the 51 sites revealed only 1.96% having excellent (>75%) live coral cover, 13.72% good (>50% to <75% cover), 35.29% fair (>25% to 50% cover), and 41.18% poor (<25% cover). Some reef areas showed a significant reduction of live coral cover from fair in 1983 to 1991 to poor to fair in 1994 to 2001. The status of these reefs and the different reef threat indicators identified put Iligan Bay reefs at a very high risk. Perhaps an integrated coastal co-management approach is the only option left to save the remaining reef in the bay.
Keywords: Coral reef status